2016
DOI: 10.1242/jeb.143727
|View full text |Cite
|
Sign up to set email alerts
|

A nicotinic acetylcholine receptor agonist affects honey bee sucrose responsiveness and decreases waggle dancing

Abstract: There was an error published in J. Exp. Biol. 215, 2022-2029 In the final sentence of paragraph 4 of 'Effects on SR' in the Results section, the total number of proboscis extensions is given, rather than percentages. The correct sentence is published below.On average, control nectar foragers had a lower mean total PER bee −1 (4.1±2.3 responses) than control pollen foragers (4.8±2.1 responses).The authors apologise for any confusion this may have caused. 2081

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…The ingestion of specific insecticides in sublethal concentrations increases sugar response thresholds (Eiri and Nieh, 2012) and affects homing in honeybees (Henry et al, 2012;Fischer et al, 2014). Herbert and co-workers (2014) have shown that chronic exposure to traces of GLY reduces responsiveness to sucrose and learning performance during olfactory PER conditioning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ingestion of specific insecticides in sublethal concentrations increases sugar response thresholds (Eiri and Nieh, 2012) and affects homing in honeybees (Henry et al, 2012;Fischer et al, 2014). Herbert and co-workers (2014) have shown that chronic exposure to traces of GLY reduces responsiveness to sucrose and learning performance during olfactory PER conditioning.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have already shown that other agrochemical compounds used for pest control, such as neonicotinoids, negatively affect honeybee gustatory sensitivity and even their dance maneuvers (Eiri and Nieh, 2012). Non-lethal doses of imidacloprid (75-1000 ppb), a neonicotinoid insecticide, which acts on cholinergic pathways of insect synaptic transmission (Gauthier, 2010), affect homing abilities (Bortolotti et al, 2003) and impair the retrieval of memory acquired during exploratory orientation flights (Fischer et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Pure water could therefore have provided a reward, not a neutral control stimulus, particularly for salts (K and phosphate) that elicited a largely aversive response at nearly all concentrations. We consequently adopted the protocol of some PER experiments with sucrose solutions (Decourtye et al, 2004;Eiri and Nieh, 2012;Lambin et al, 2001) and did not intersperse pure water presentations between test solution presentations.…”
Section: Per Measurements Of Honey Bee Salt Preferencesmentioning
confidence: 99%
“…Exposure to imidacloprid and thiamethoxam has also been shown to increase the honey bee sucrose response threshold (lowest sucrose percentage that elicits PER), as an indicator of decreased appetitive motivation and selective foraging for sweeter food sources, at doses of 0.21-2.16 ng imidacloprid/bee and 1 ng thiamethoxam/bee (Aliouane et al, 2009;Eiri and Nieh, 2012). Preference for sweeter nectar sources leads to reduced or more selective foraging by bees and is causally linked to division of labor of foraging (i.e., water, nectar, or pollen foraging) (Pankiw and Page, 2000).…”
Section: Consideration Of Biological Plausibility and Empirical Supportmentioning
confidence: 99%
“…Therefore, studies reporting increased sucrose response thresholds and decreased appetitive motivation indicate that the colony food supply would be negatively impacted due to the lower quality of nectar collected and the greater effort needed to process that nectar into stored honey (Drezner-Levy et al, 2009;Eiri and Nieh, 2012). Finally, the waggle dance, which requires learning and memory as well as coordination, was shown to be impacted by exposure to 0.21 ng imidacloprid/bee, with treated animals performing between 4.5 and 10.5-fold fewer dance circuits compared to controls (Eiri and Nieh, 2012).…”
Section: Consideration Of Biological Plausibility and Empirical Supportmentioning
confidence: 99%